Bulb and Root Rot in Lily (Lilium longiflorum) and Onion (Allium cepa) in Israel. Issue 7 (3rd January 2014) - Lebiush‐Mordechai, Sara; Erlich, Orly; Maymon, Marcel; Freeman, Stanley; Ben‐David, Tslila; Ofek, Tal; Palevsky, Eric; Tsror (Lahkin), Leah
Abstract In the past 10 years, there has been a substantial increase in reports, from growers and extension personnel, on bulb and root rots in lily (Lilium longiflorum) in Israel. Rot in these plants, when grown as cut flowers, caused serious economic damage expressed in reduction in yield and quality. In lily, the fungal pathogens involved in the rot were characterized as binucleate Rhizoctonia AG‐A, Rhizoctonia solani, Pythium oligandrum, Fusarium proliferatum (white and purple isolates) and F. oxysporum, using morphological and molecular criteria. These fungi were the prevalent pathogens in diseased plants collected from commercial greenhouses. Pathogenicity trials were conducted on lily bulbs and onion seedlings under controlled conditions in a greenhouse to complete Koch's postulates. Disease symptoms on lily were most severe in treatments inoculated with binucleate Rhizoctonia AG‐A, P. oligandrum and F. proliferatum. Plant height was lower in the above treatments compared with the control plants. The least aggressive fungus was R. solani. In artificial inoculations of onion, seedling survival was significantly affected by all fungi. The most pathogenic fungus was F. proliferatum w and the least were isolates of F. oxysporum (II and III). All fungi were successfully re‐isolated from the inoculated plants.